2005
DOI: 10.1038/sj.emboj.7600621
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of neuronal positions in organized ganglia by SAX-7, a Caenorhabditis elegans homologue of L1

Abstract: The L1 family of cell adhesion molecules is predominantly expressed in the nervous system. Mutations in human L1 cause neuronal diseases such as HSAS, MASA, and SPG1. Here we show that sax-7 gene encodes an L1 homologue in Caenorhabditis elegans. In sax-7 mutants, the organization of ganglia and positioning of neurons are abnormal in the adult stage, but these abnormalities are not observed in early larval stage. Misplacement of neurons in sax-7 mutants is triggered by mechanical force linked to body movement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
116
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(137 citation statements)
references
References 75 publications
(129 reference statements)
15
116
0
2
Order By: Relevance
“…Given the zig-4 precedent and the expression of at least six of the eight zig genes in the PVT neuron of the ventral nerve cord (Aurelio et al 2002), we analyzed ventral nerve cord architecture in all zig mutant animals. In addition, we also examined the correct position of neuron soma; correct maintenance of soma position is controlled by other previously identified maintenance factors (Zallen et al 1999;Sasakura et al 2005;Bénard et al 2006). This neuroanatomical analysis was conducted by crossing a series of chromosomally integrated gfp reporters that allow the visualization of individual neuron types in all zig mutant backgrounds (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the zig-4 precedent and the expression of at least six of the eight zig genes in the PVT neuron of the ventral nerve cord (Aurelio et al 2002), we analyzed ventral nerve cord architecture in all zig mutant animals. In addition, we also examined the correct position of neuron soma; correct maintenance of soma position is controlled by other previously identified maintenance factors (Zallen et al 1999;Sasakura et al 2005;Bénard et al 2006). This neuroanatomical analysis was conducted by crossing a series of chromosomally integrated gfp reporters that allow the visualization of individual neuron types in all zig mutant backgrounds (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Its precisely mapped and invariantly structured nervous system allows to probe with unprecedented detail the effect of removing individual cells and genes. Genetic and cellular ablation studies have revealed that a number of diverse Ig domain proteins are required to maintain the precise positioning of axons within fascicles and cell bodies within ganglia (Zallen et al 1999;Aurelio et al 2002;Bü low et al 2004;Sasakura et al 2005;Wang et al 2005;Bénard et al 2006;Pocock et al 2008). Intriguingly, without these molecules nervous system development is unaffected, yet precise neuroanatomical patterns are lost postdevelopmentally.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The locations of neuronal soma, axons, and dendrites must be maintained to ensure proper nervous system function during the addition and removal of neurons and synapses and in response to mechanical stresses associated with body growth and movement. The factors maintaining nervous system architecture are often distinct from those involved in its establishment during development, a division of labor which likely allows flexibility to cope with the stresses involved in remodeling, growth, and movement.The involvement of extracellular matrix components, cell adhesion molecules, and cytoskeletal proteins in previously reported neural maintenance activities demonstrate that adhesive cell-matrix and possibly cell-cell interactions play a critical role (Aurelio et al 2002;Bulow et al 2004;Sasakura et al 2005;Wang et al 2005;Benard et al 2006Burket et al 2006;Pocock et al 2008;Woo et al 2008; Zhou et al 2008). Although previously unreported, factors controlling nuclear position in neurons may also be predicted to play key roles in positional maintenance of neuronal soma.…”
mentioning
confidence: 97%
“…The involvement of extracellular matrix components, cell adhesion molecules, and cytoskeletal proteins in previously reported neural maintenance activities demonstrate that adhesive cell-matrix and possibly cell-cell interactions play a critical role (Aurelio et al 2002;Bulow et al 2004;Sasakura et al 2005;Wang et al 2005;Benard et al 2006Burket et al 2006;Pocock et al 2008;Woo et al 2008; Zhou et al 2008). Although previously unreported, factors controlling nuclear position in neurons may also be predicted to play key roles in positional maintenance of neuronal soma.…”
mentioning
confidence: 97%